Drought-triggered leaf transcriptional responses disclose key molecular pathways underlying leaf water use efficiency in sugarcane (Saccharum spp.) - Contiliani, Danyel F.; Nebó, João Felipe C. de O.; Ribeiro, Rafael V.; Landell, Marcos G. de A.; Pereira, Tiago C.; Ming, Ray; Figueira, Antonio; Creste, Silvana (Frontiers in Plant Science, 2023)
Drought is a major constraint to sugarcane (Saccharum spp.) production, and improving the water use efficiency (WUE) is a critical trait for the sustainability of this bioenergy crop. The molecular mechanism underlying WUE remain underexplored in sugarcane. Here, we investigated the drought-triggered physiological and transcriptional responses of two sugarcane cultivars contrasting for drought tolerance, ‘IACSP97-7065’ (sensitive) and ‘IACSP94-2094’ (tolerant). After 21 days without irrigation (DWI), only ‘IACSP94-2094’ exhibited superior WUE and instantaneous carboxylation efficiency, with the net CO2 assimilation being less impacted when compared with ‘IACSP97-7065’. RNA-seq of sugarcane leaves at 21 DWI revealed a total of 1,585 differentially expressed genes (DEGs) for both genotypes, among which ‘IACSP94-2094’ showed 617 (38.9%) particular transcripts (212 up- and 405 down-regulated). Functional enrichment analyses of these particular DEGs revealed several relevant biological processes, such as photosynthesis, transcription factors, signal transduction, solute transport, and redox homeostasis. The better drought-responsiveness of ‘IACSP94-2094’ suggested signaling cascades that foster transcriptional regulation of genes implicated in the Calvin cycle and transport of water and carbon dioxide, which are expected to support the high WUE and carboxylation efficiency observed for this genotype under water deficit. Moreover, the robust antioxidant system of the drought-tolerant genotype might serve as a molecular shield against the drought-associated overproduction of reactive oxygen species. This study provides relevant data that may be used to develop novel strategies for sugarcane breeding programs and to understand the genetic basis of drought tolerance and WUE improvement of sugarcane.